Template for Standardized Description of Sustainable Land Management (SLM) Technologies with a Focus on Field-Landscape Level. - Le, Quang Bao (2017)
This off-line CRP-DS/ICARDA template of SLM technology description is partly adapted from those of WOCAT, however with major modifications and additions. It has six (6) main parts. The information fields that are inherited and modified from the WOCAT template are marked with WOCAT (Note: Inherited from WOCAT) and MW (Note: Modifed from WOCAT), respectively. All new fields are kept unmarked. All compulsory fields are highlighted with a red asterrisk (*). This off-line template was developed for the uses of SLM-related projects of CRP-DS, ICARDA and their partners that were indexed and monitored by MEL platform (https://mel.cgiar.org/). Attempts to share this tool with other individuals/projects/organizations need to be agreed by, and eventually done through Quang Bao Le (q.le@cgiar.org) and Enrico Bonaiuti (e.bonaiuti@cgiar.org).